PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM MBKM MEMBANGUN DESA/KKN AKHLAKUL KARIMAH DI DUSUN IV SUKOHARJO 2 - Yuhandini, Anita (Jurnal Pengabdian Kepada Masyarakat Ungu (ABDI KE UNGU), 2025)
The Community Service Program (KKN) ois an academic acivity aimed at enhancing at enhancing students' skills while empowering local communities. The MBKM Village Development/KKN Akhlakul Karimah program in Dusun IV Sukoharjo II includes health education, religious literacy enhancement, economic empowerment, and environmental cleanliness initiatives. Activities carried out in this program include health counseling, free medical check-ups, training on family medicinal plants (TOGA) cultivation, strengthening moral values, and economic empowerment through fisheries and agriculture. The results indicate an increase in health awareness, improved cultivation skills, and heightened community enthusiasm for religious education. This program is expected to provide sustainable benefits through active community participation and support from local government authorities.